Influence of methylenetetrahydrofolate reductase gene polymorphisms on the outcome of pediatric patients with non-Hodgkin lymphoma treated with high-dose methotrexate. Issue 12 (December 2013) - D'Angelo, Velia; Ramaglia, Maria; Iannotta, Adriana; Francese, Matteo; Pota, Elvira; Affinita, Maria Carmen; Pecoraro, Giulia; Indolfi, Cristiana; Di Martino, Martina; Di Pinto, Daniela; Buffardi, Salvatore; Poggi, Vincenzo; et al.
Abstract High-dose methotrexate (MTX) is a key component of most treatment protocols for childhood and adolescent non-Hodgkin lymphoma (NHL). Recent studies have suggested that the toxicity of antifolate drugs, such as MTX, is affected by inherited single nucleotide polymorphisms (SNPs) in folate metabolizing genes. The aim of our study was to investigate the potential influence of the C677T and A1298C genetic variants of the methylenetetrahydrofolate reductase (MTHFR) gene on the clinical toxicity and efficacy of MTX in pediatric patients with NHL (n = 95) treated with therapeutic protocols Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) LNH-97 and EURO LB-02. We demonstrated that patients with the 677T genotype had an approximately six-fold greater risk of developing hematological toxicity compared with wild-type carriers, especially in the 1 g/m2 treatment group (p = 0.01). Moreover, we identified a correlation between the risk of relapse and the T genotype: T carriers had reduced disease-free survival compared with wild-type patients (67% vs. 100%). Our data suggest a pharmacogenetic influence on the adverse effects of high-dose MTX in the 1 g/m2 treatment group.